Gene expression profiling of laser microdissected airway smooth muscle tissue in asthma and atopy. Issue 9 (19th July 2014) - Yick, C. Y.; Zwinderman, A. H.; Kunst, P. W.; Grünberg, K.; Mauad, T.; Chowdhury, S.; Bel, E. H.; Baas, F.; Lutter, R.; Sterk, P. J.
Abstract Background Asthma and atopy share common characteristics including type 2 helper‐T‐cell‐mediated inflammation. However, only asthma is associated with variable airways obstruction. The complex cellular and molecular pathways distinguishing asthma and atopy can now be captured by transcriptomic analysis (RNA‐Seq). We hypothesized that the transcriptomic profile of airway smooth muscle (ASM) distinguishes atopic asthma from atopic healthy controls. First, we compared the ASM transcriptomic profiles of endobronchial biopsies between glucocorticoid‐free, atopic asthma patients, and atopic and nonatopic healthy controls. Second, we investigated the association between ASM transcriptomic profiles and airway function. Methods Twelve asthma patients and 12 control subjects (six atopic, six nonatopic) underwent bronchoscopy. RNA of laser‐dissected ASM from 96 bronchial biopsy specimens was sequenced with Roche GS FLX. Gene networks were identified using Ingenuity Pathway Analysis. RNA‐Seq reads were assumed to follow a negative binomial distribution. With the current sample size, the estimated false discovery rate was approximately 1%. Results One hundred and seventy four ASM genes were differentially expressed between asthma patients and atopic controls, 108 between asthma patients and nonatopic controls, and 135 between atopic and nonatopic controls. A set of eight genes discriminated asthma patients from nonasthmatic controls, irrespective of atopy. Four of these genes (RPTOR, VANGL1, FAM129A, LEPREL1) were associated with airway hyper‐responsiveness (P < 0.05). Conclusion Airway smooth muscle from asthma patients can be distinguished from that of atopic and nonatopic control subjects by a specific gene expression profile, which is associated with airway hyper‐responsiveness.